2022
DOI: 10.1002/ldr.4306
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ecological restoration on carbon sink and carbon drawdown of degraded salt marshes with carbon‐rich additives application

Abstract: Plant biomass resources have been gradually used to restore and improve saline soils. However, little is known about whether the applications of reed straw (PA) and biochar (BC) in degraded coastal salt marshes are beneficial for blue carbon sink enhancement and carbon drawdown. Here, we evaluated the effects of 3% PA and 3% BC applications on the vegetation, soil and blue carbon sink function of degraded salt marsh ecosystems and assessed their CO2 reduction capacities based on the life cycle. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Over half of organic matter production in saltmarsh plants occurs in roots and rhizomes that are buried within the soil (Duarte et al, 2013) and lower dry bulk densities have been associated with high biomass and abundance of roots in saltmarsh plant species (Santini et al, 2019), hence the inverse relationship when carbon stock is higher at lower bulk densities observed across coastal blue carbon habitats (Dahl et al, 2016;Barry et al, 2018;Gao et al, 2019;Lima et al, 2020). In turn, root biomass is known to contribute significantly to carbon stocks (Jones and Donnelly, 2004;Ford et al, 2019;Santini et al, 2019;Chen et al, 2022) and has been shown to be significantly lower in pioneer communities than for plant communities at higher elevations across UK saltmarshes (Harvey et al, 2019).…”
mentioning
confidence: 99%
“…Over half of organic matter production in saltmarsh plants occurs in roots and rhizomes that are buried within the soil (Duarte et al, 2013) and lower dry bulk densities have been associated with high biomass and abundance of roots in saltmarsh plant species (Santini et al, 2019), hence the inverse relationship when carbon stock is higher at lower bulk densities observed across coastal blue carbon habitats (Dahl et al, 2016;Barry et al, 2018;Gao et al, 2019;Lima et al, 2020). In turn, root biomass is known to contribute significantly to carbon stocks (Jones and Donnelly, 2004;Ford et al, 2019;Santini et al, 2019;Chen et al, 2022) and has been shown to be significantly lower in pioneer communities than for plant communities at higher elevations across UK saltmarshes (Harvey et al, 2019).…”
mentioning
confidence: 99%
“…Meanwhile, analysis methods included multiple innovation model combinations as well as meta‐analysis. SD: system dynamics, GIS: geographic information systems, RF Model: random forest model, DNDC Model: denitrification‐decomposition (DNDC) model (Bhardwaj et al, 2022; Chen et al, 2022; Feng et al, 2023, Hashimi et al, 2022; He et al, 2022; Jia et al, 2023; Liu et al, 2022; Ravisankar et al, 2022; Wang et al, 2022, 2023; Xu et al, 2022; Yang et al, 2022, Zhang et al, 2022, 2023). [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Figurementioning
confidence: 99%
“…Similarly, the natural vegetation saxaul ( Haloxylon ammodendron ) alleviates desertification better than the artificially planted matrimony vine ( Lycium barbarum L.) in desert ecosystems (Yang et al, 2022). Reed straw ( Phragmites australis ) application effectively improved degraded salt marshes and enriched carbon sinks (Chen et al, 2022). Moreover, salt‐tolerant grasses, in partnership with arbuscular mycorrhizal fungi, can potentially rehabilitate heavy metal‐contaminated saline ecosystems (Jia et al, 2023); this finding suggests that ecological engineering is developing sustainably.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to plant photosynthesis, wetland sediment is also a main carbon storage sink in the salt marsh ecosystem. Studies have shown that reed straw and biochar can effectively restore degraded salt marshes and enhance blue carbon sinks (Chen et al, 2022). The carbon sequestration in the seagrass bed ecosystem includes a high productivity of seagrass bed plants, clastic carbon capture ability in seawater, and lower decomposition of sediments (Lee et al, 2021).…”
Section: Introductionmentioning
confidence: 99%